Sosialisasi Pembuatan Shopee Merchant ShopeeFood pada UMKM Perumahan Sudirman Indah Tigaraksa - Rismanto, Caesar; Ahmad Rasyiddin; Febri Sari Siahaan; Ibrahim Tri Nugroho (Universitas Tangerang Raya, 2024)
This research aims to evaluate the effectiveness of socializing the creation of Shopee Merchant ShopeeFood to MSMEs in the Sudirman Indah Tigaraksa Housing Complex. Digitalization of MSMEs is becoming increasingly important in the era of the digital economy, and ShopeeFood offers a platform that can expand the market for local MSMEs. Using qualitative methods, this research collected data through in-depth interviews and observations of MSME actors who participated in the socialization program. Thematic analysis was applied to identify the main themes that emerged from the data collected. The research results show that this socialization was successful in increasing MSMEs' understanding and technical skills in using the ShopeeFood platform. MSMEs report improvements in operational efficiency and wider market access after joining ShopeeFood. However, several challenges such as limitations in technology access and digital awareness still hinder the optimization of platform use. This research concludes that although this outreach has a positive impact, continued support is needed from Shopee and the government to overcome existing obstacles. Recommendations are given to improve continuous training, strengthen digital infrastructure, and provide incentives for MSMEs to make maximum use of digital platforms. The findings of this research provide important insights for MSME development strategies in the digital era and suggest future research directions to explore the long-term impact of digital technology adoption by MSMEs.